Analisa Quality Of Service (QoS) Trafik Multimedia Pada Pemodelan Jaringan Multiprotocol Label Switching (MPLS) Menggunakan Router Mikrotik - Gozali, M Moriandy; Sari, Linna Oktaviana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Quality of Service (QoS) is a performance indicator on many communication systems. The Multiprotocol Label Switching (MPLS) is a part of the communication system. One of approach to find out QoS performance indicator for MPLS is using of a Mikrotik router. The network testing scenario using bus topology, where different types of traffic is delivered audio and video streaming that has a variety of different file sizes. The first scenario involving 1 client to send and the other scenario involving 2 client to send. The result show that MPLS network meets ITU-T G.114 standards where the average accepted delay for packet data transmission is less than 150 ms, in the simulation results indicates that the delay value is below of 150 ms in both scenarios. The value of packet loss based on ITU-T G.1010 standard is less than 1% where the simulation results indicate that packet loss value is below 1% in both scenarios. Overall, the MPLS network is proven to serve a heavy multimedia traffic.Keywords : MPLS, OSPF, QoS, multimedia traffic